Echocardiographic evaluation of cardiac function among male adolescents at high risk of coronary heart disease - Alaaeldin A. H. Mahmoud; Mohammed E. M. Abdelgawad; Walid A. a. Elmorsy; Mohammed S. Al-khayat; Noha M. Elbadry (Al-Azhar Assiut Medical Journal)
Background and aim Obesity, and family history (smoking, obesity, and hypertension) are the most important risk factors for the development of coronary heart disease (CHD) among adolescents. The study aims to evaluate the cardiac function among male adolescents at high risk for coronary heart disease. Patients and methods A total of 100 male adolescents were selected by written questionnaire in addition to 30 normal adolescents as control. Thorough history taking and physical examination. Echocardiographic examination, serum lipids, and routine laboratory investigations. Results Obesity, and a family history of (smoking, hypertension, and obesity) are among the most frequent risk factors for CHD among male adolescents. We found a statistically significant elevated concentration of serum cholesterol and triglyceride and a significant decrease in high-density lipoprotein levels among diabetic and hypertensive children in addition to a significantly elevated concentration of serum low-density lipoprotein among hypertensive children and children with a sedentary lifestyle. The echocardiography reflects a significant increase in early and decreases in late diastolic flow velocity (E and A) among hypertensive and obese adolescents versus controls. A statistically significant differences between diabetics and controls for left ventricular posterior wall diameter, inter-ventricular septal diameter, and early and late diastolic flow velocity. Conclusion Obesity and a family history of smoking, obesity, and hypertension are among the most frequent risk factors for CHD among male adolescents. Echocardiography and lipid profiles should be performed for any adolescent at high risk for development of CHD.